A Proposed Intervention Model for the Papua Conflict to Promote Conflict Resolution and Peacebuilding - Ilham Fakih Mullah; Prihartoro, Mitro; Arbiansyah, Tri Panca Titis; Setiawibawa, Rachmat (Cita konsultindo, 2025)
The government's efforts to handle armed group activities often result in casualties. Resolving the dynamic conflicts in Papua requires synergy among relevant parties such as state institutions, ministries, and experts in their respective fields. Resolving conflicts in Papua is a form of implementing the concept of national security. This research will examine the relationship between conflict intervention and conflict resolution in Papua, which influences the formulation of Papua conflict intervention designs aimed at building conflict resolution and peace. The method used in this research is qualitative research, with the conflict in Papua as the object of study through the collection of empirical and theoretical literature analyzed to build resolution and peace. Peace in Papua can be achieved through conflict management processes consisting of conflict de-escalation, humanitarian intervention and political negotiation, problem-solving approaches, and peacebuilding. Intervention strategies must ensure that program impacts reach the entire Papua community. The importance of intervening in Papua's conflict is seen as a comprehensive improvement process for security policies in Papua